Cell cycle block by p53 activation reduces SARS-CoV-2 release in infected alveolar basal epithelial A549-hACE2 cells - Lodi, Giada; Gentili, Valentina; Casciano, Fabio; Romani, Arianna; Zauli, Giorgio; Secchiero, Paola; Zauli, Enrico; Simioni, Carolina; Beltrami, Silvia; Fernandez, Mercedes; Rizzo, Roberta; Voltan, Rebecca (Frontiers in Pharmacology, 2022)
SARS-CoV viruses have been shown to downregulate cellular events that control antiviral defenses. They adopt several strategies to silence p53, key molecule for cell homeostasis and immune control, indicating that p53 has a central role in controlling their proliferation in the host. Specific actions are the stabilization of its inhibitor, MDM2, and the interference with its transcriptional activity. The aim of our work was to evaluate a new approach against SARS-CoV-2 by using MDM2 inhibitors to raise p53 levels and activate p53-dependent pathways, therefore leading to cell cycle inhibition. Experimental setting was performed in the alveolar basal epithelial cell line A549-hACE2, expressing high level of ACE2 receptor, to allow virus entry, as well as p53 wild-type. Cells were treated with several concentrations of Nutlin-3 or RG-7112, two known MDM2 inhibitors, for the instauration of a cell cycle block steady-state condition before and during SARS-CoV-2 infection, and for the evaluation of p53 activation and impact on virus release and related innate immune events. The results indicated an efficient cell cycle block with inhibition of the virion release and a significant inhibition of IL-6, NF-kB and IFN-λ expression. These data suggest that p53 is an efficient target for new therapies against the virus and that MDM2 inhibitors deserve to be further investigated in this field.